Knowledge and utilization of family planning and safe abortion services among married women of reproductive age in the Raute community of Nepal: A census-based cross-sectional study - Manoj Joshi; Anjali Bhatt; Anusha Sharma; Milan Thapa; Sudip Khanal (PLOS Global Public Health, 2026)
Raute the last nomadic hunter-gatherer marginalized indigenous group face disproportionate and persistent barriers to reproductive health services, including family planning and safe abortion. The lack of the pre-existing population-level quantitative reproductive health data limits the ability of health authority to design cultural-sensitive health services. This census-based cross-sectional study enrolled all 192 eligible married women of reproductive age in the Raute community of Parshuram Municipality, Dadeldhura district, Sudurpaschim Province, Nepal. Data was collected through structured interviews, and analyzed in IBM SPSS version 16. Results showed more than half of participants (53.6%) currently used family planning, with injectable contraceptives being the most common method (42.7%), followed by female sterilization (33.0%) and implants (24.3%), while condom use was negligible at 1.0%. Among non-users (46.4%), 97.7% cited lack of interest as the primary reason. Knowledge of safe abortion services was reported by 61.5% of women, yet only 8.3% had ever accessed such services, and awareness of Nepal's national safe abortion policy was critically low (10.4%). The independent predictor of current family planning utilization in the adjusted logistic regression model was non-utilization of safe abortion services (AOR = 4.275; 95% CI: 1.145–15.954; p = 0.030), suggesting that contraceptive use and abortion service use represent alternative reproductive management strategies in this community. Younger age (≤30 years) and urban residence were significantly associated with safe abortion use in bivariate analysis but were attenuated after adjustment. These findings reveal critical gaps in reproductive method diversity, safe abortion policy literacy, and male partner engagement. Community-based mobile outreach tailored to nomadic movement patterns, legal literacy programs in the local language, and strategies to engage male partners are indicated as priorities; their design should be informed by qualitative, community-engaged research into the cultural and relational dynamics that a structured survey cannot capture.